Business Plan : Beany Cafe / Muhammad Qayyum Mohd Azman …[et al.] - Mohd Azman, Muhammad Qayyum; Mohd Azmi, Amalin Aliesya; Wan Ahmad, Wan Nurul Ain; Ismail, Nur Nabila; Rusdi, Muhamad Anif Ikmal (2021)
This business is based on partnership where it consists of five (5) members which hold important positions in the company such as General Manager, Marketing Manager, Operational Manager and Financial Manager. The business capital is amounted to RM600,000 where the total contribution of each member is RM100,000 and the rest RM100,000 is from Bank Islam’s loan. Caramel Macchiato coffee is one of the best sales and popular among customer at our Beany Café. Beany Café with the tagline “Coffee 4Liferrr” is located near with Bandar Baru Bangi address: Beany Café, Bangi Sentral, 43650 Bandar Baru Bangi, Selangor. Beany Café is a company which focuses on food and drink production in Malaysia. Coffee and dessert are one of the most popular among teenager especially someone who are in love with something sweet. Differences in size and categories make it more affordable for everyone even students. Dessert at Beany Café always attract our customer because the size and shape make this dessert looks interesting and suitable to serve for any occasion. The light and sweetness of chocolate gives opportunity to this dessert to be one of marketable product as people love something sweet especially the ingredient is chocolate. Moreover, the simple steps and ingredients give a lot of benefits to our company and we are highly confident that our market can be easily developed and spread in Malaysia. To make it more attractive and interesting, we decide to make some innovation by implying our creativity and modern element in coffee and dessert. Nowadays, design is one the important thing in any product because the unique product making more customers attract with dessert at Beany Café. We have done some research that Malaysia that Malaysia is one of developed country and it quite busy during day time. Normally people who work during office hour and students do not have much time for breakfast. So, with our new innovation, our customer can buy our coffee in a cup of bottle and can keep in their refrigerator and bring to their work or school. We also attract our customer during lunch hour because they come to relieve stress with our coffee and dessert. The peaceful environment at Beany Café can help them relieve stress with their work while enjoying coffee. Based on the objective above, we are venturing into drink and food industry. Beany Café production has potential of being profitable business if it is done with more Beany Café branch in a large scale and systematically managed. We will expect that our Beany Café business will become more developed in the near future because with new innovation in our coffee and dessert, the demand will increase not only during any occasion but it might be a new daily routine for our customer to bring their coffee at work. This will give more advantages for our business to make a product more profitable and stable in the long run.